An economical means for remediating a multiple-metal contaminated soil using electro-kinetic technology under natural conditions - Saleem, Muhammad; Essa, M.H.; Chakrabarti, Mohammed Harun; Low, C.T.J.; Hajimolana, S.A.; Hussain, Mohd Azlan; Hashim, M.A.; Islam, M.S. (Electrochemical Science Group, 2012)
A bench-scale study on the improved electro-kinetic remediation of heavy metals from soil collected near an operating electroplating site in Pakistan is reported. Influence of operating parameters such as electrode material, current density, soil temperature and inter-electrode spacing is investigated. A maximum of 61.8 removal of cadmium is achieved using titanium electrodes (under natural conditions simulating rain water present in soil). Removal efficiency improves with the increase in current density and soil temperature. About 73 of copper removal is achieved within 20 hours when the soil temperature is constant at 29Â°C as compared to 32 removal at 18Â°C. Rate of metal removal increases as the inter-electrode spacing decreases to 10 cm, which demonstrates the highest copper removal of 88.1 at a current density of 8.9 mA/cm2. Other heavy metals are well below their maximum permissible limits and thus are not studied in detail. A maximum energy consumption of 5 kWh/m3 of soil means the process can be economically scaled up. Removal efficiencies may be improved by carefully controlling the catholyte pH and by introducing zero-valent iron particles as a permeable reactive barrier in the electro-kinetic process.